Total quality management practices in Turkish primary schools - Toremen, Fatih; Karakus, Mehmet; Yasan, Tezcan (Emerald Group Publishing Ltd, 2009)
Purpose - The purpose of this paper is to determine the extent of total quality management (TQM) practices in primary schools based on teachers' perceptions, and how their perceptions are related to different variables. Design/methodology/approach - In this study, a survey based descriptive scanning model was used. This study was carried out in Malatya city centre on teachers working at primary schools. Using stratified sampling method, 21 schools and 420 teachers working in these schools were selected randomly. A total of 396 of the questionnaires were validated and evaluated. A total of six-dimensioned and a 60-itemed questionnaire was administered to these teachers. Data were analysed by SPSS program. Findings - In the perceptions of teachers, there were some problems with the indicators of TQM practices, especially on the dimension of change management. There were significant differences among teachers' perceptions on TQM practices depending upon the variables of branch, level of education and tenure, while there were no meaningful differences according to the gender variable. Practical implications - The findings reveal the need for an effective change management, educating staff and utilizing human resources to attain a system-wide quality improvement, to implement the principles of TQM. Originality/value - Quality improvement is a continual process that should be taken up from the operational level to senior management. Primary schools, as the basic subsystem of educational super-system, affect upper level schools with their outcomes. So TQM efforts at primary schools are fundamentally important to achieve a high quality education system. This paper sheds light on how to improve quality at this basic level.
Keywords: Total quality management; Primary schools; Teachers; Turkey